Electrophysiological correlates of reading the single- and interactive-mind - Yi-Wen eWang; Yu-Wei eZheng; Chong-De eLin; Jie eWu; De-Li eShen (Frontiers in Human Neuroscience, 2011)
Understanding minds is the cognitive basis of successful social interaction. In everyday life, human mental activity often happens at the moment of social interaction among two or multiple persons instead of only one person. Understanding the interactive mind of two- or multi-person is more complex and higher than understanding the single-person mind in the hierarchical structure of theory-of-mind. Understanding the interactive mind maybe differentiate from understanding the single mind. In order to examine the dissociative electrophysiological correlates of reading the single mind and reading the interactive mind, the 64 channels event-related potentials (ERP) were recorded while 16 normal adults were observing three kinds of Chinese idioms depicted physical scenes, one-person with mental activity and two- or multi-person with mental interaction. After the equivalent N400, in the 500- to 700-ms epoch, the mean amplitudes of late positive component (LPC) over frontal for reading the single mind and reading the interactive mind were significantly more positive than for physical representation, while there was no difference between the former two. In the 700-to 800-ms epoch, the mean amplitudes of LPC over frontal-central for reading the interactive mind were more positive than for reading the single mind and physical representation, while there was no difference between the latter two. The present study provides electrophysiological signature of the dissociations between reading the single mind and reading the interactive mind.